The influence of mobile environmental cues on purchasing intention and positive user-generated content spread in instagram context / Azlin Zanariah Bahtar - Bahtar, Azlin Zanariah (2019)
Generation-Y (GenY) makes up the largest population of Malaysia. This generation is different as compared to generations before them as they are born with innovated technology, grow up with the internet and active on social media; either for networking purpose or to facilitate them in purchasing. GenY prefers to refer contents uploaded by other social media users when deciding to purchase. It is believing, the contents uploaded are truthful and unbiased. Sellers are aware that contents uploaded are uncontrollable, and not always in favour of them. Therefore, many sellers have opted to conduct their social media marketing strategies as efforts to create better customer engagements with hopes to attract purchases and to only spread positive words about their brands and product. Stimulus-Organism-Responses (SOR) Model by Eroglu et al. (2001) is adopted in this study along with other relevant and related models to examine the impact of mobile environmental cues (page image layout, information, privacy, and shaped discussion) on customers' cognitive (perceived usefulness and perceived ease of use), and affective (arousal and pleasure) states that in turn, influence their purchase intention and positive user-generated content (UGC) spread. Purposive sampling technique is employed, and respondents (N = 207) were among Instagram users who have experiences in conducting purchases via Instagram within 12 months. Data were analysed using Partial Least Square (PLS-SEM) technique. The results obtained revealed that mobile environmental cues influence one's responses after going through organism (cognitive and affective). Although information is assumed to be very important for digital marketing and selling, yet findings showed information did not have positive or significant relationships with organism variables. Shaped discussion was found to be more impactful on organism variables which influences Instagram users to conduct purchasing via mobile and to spread good contents. Meanwhile, arousal was found to be the most influential organism variable on purchase intention. Findings of this study highlighted that engagements and relationships between online buyers and sellers are important in order to make sellers to be more competitive and sustain in conducting their businesses.